Examining preservation priorities for the audiovisual collection of the media services section of the University of the Philippines Diliman main library - Cordova, Vanessa Gem T. (2016)
The main purpose of academic libraries is to provide the research needs of the students, faculty and staff and support the institution's curriculum. To achieve that, the library must have all the resources that their users might used in through different media formats. Aside from circulating the audiovisual materials, the libraries must deliberately preserve their collection.